Pemberdayaan Penyandang Disabilitas melalui Hilirisasi Produk Unit Mikro, Kecil, dan Menengah - Rispatiningsih, Dwi Maryani; Lery Prasetyo; Sulaiman, Sulaiman; Marjianto, Marjianto; Ari Mariyono; Eko Siswoyo; Mugiyo, Mugiyo; Ayuning Wulan (Insan Kreasi Media, 2025)
This community engagement project aims to describe the empowerment of persons with disabilities through the downstreaming of MSME (Micro, Small, and Medium Enterprise) products in Wonogiri Regency. The primary issues identified include the low level of participation of persons with disabilities in productive economic activities and the suboptimal implementation of inclusive MSME downstreaming. The project employed the Asset-Based Community Development (ABCD) approach. The findings indicate that persons with disabilities possess significant potential to engage in various downstreaming stages, such as packaging, product finishing, basic design, and digital marketing. Nevertheless, structural, cultural, and technical barriers continue to impede their full integration. This project proposes an inclusive empowerment model based on MSME downstreaming that integrates competency-based training, continuous mentoring, adaptive facilities, and collaboration among MSMEs, local government, and disability communities. These findings are expected to serve as policy recommendations for strengthening inclusive economic development in Wonogiri Regency.